Testing the optimal defense hypothesis in Stryphnodendron adstringens (Fabaceae, Mimosoideae) leaves: the role of structure, number, position and nectar composition of extrafloral nectaries - Delgado, Marina N.; Somavilla, Nádia S.; Báo, Sônia N.; Rossatto, Davi R. [UNESP] (Wiley, 2017)
Stryphnodendron adstringens is a common Cerrado tree that possesses extrafloral nectaries (EFNs) on its leaves, which are located at the base and apex of the rachis and along the secondary veins. The position of EFNs and their nectar production can be affected by defense strategies because plant organs possess different values and herbivory vulnerability. Here we aimed to elucidate anatomy, histochemistry, nectar composition and EFN number on leaves of S. adstringens in the light of the optimal defense hypothesis. We found a convergence on anatomy and histochemical characterization because the three studied types of EFNs have epidermis, secretory parenchyma and vascular tissue, showing phenolic compounds and polysaccharides in the secretory parenchyma cells. The nectar contained glucose, fructose and sucrose, which attract ants of the Camponotus and Cephalotes genus. We found differences in the number of EFNs along the secondary veins and in the nectar composition between EFNs located at the base and apex of the rachis of the leaf. The number of EFNs on the secondary veins increases from the base to the apex, suggesting a strategy to induce ant patrolling over the entire leaf region. EFNs at the base secreted more nectar, which should be related to the protection of the leaf base, which is the part most vulnerable to herbivore attack and the most valued organ. We concluded that EFNs of S. adstringens are anti-herbivore defenses whose pattern matches the predictions of the optimal defense hypothesis.
Keywords: ant patrolling; Cerrado; inducible defense; morphology; nectar chemistry